Assessment of cool-season turfgrass sod production characteristics of tall fescue and Kentucky bluegrass - Nwachukwu, Emmanuel Uzoma (My University, 2025)
The demand of high quality turfgrass cool-season sod is increasing in the transition and northern climatic zones of the United States. Genetic variation exists among Kentucky bluegrass (Poa pratensis L.) (KB) cultivars and tall fescue (Festuca arundinacea Schreb.) (TF) is gaining popularity to be used for sod, but the bunch type growth habit creates a limitation. My objectives in Chapter 2 were to: 1) quantify the influence of nine KB cultivars of varying classifications mixed with TF in a 95:5 (w/w) mixture ratios; and 2) quantify the influence of three KB cultivars of varying growth aggressiveness levels mixed in varying TF:KB mixtures of 97:3, 95:5, and 90:10 (w/w); on sod strength, ecological dynamics, and establishment vigor. My objectives in Chapter 3 and 4 were to quantify the speed of germination, establishment vigor, rhizome characteristics, as well as sod strength and handling of KB classifications (Shamrock, Compact, Jefferson etc.) and seven rhizomatous tall fescue (RTF) cultivars, respectively. In Chapter 2, results revealed KB classifications or growth aggressiveness level in sod varying ratios (90:10, 95:5, or 97:3 TF:KB w/w) produced similar-to-no differences in sod strength and handling across multiple harvests (12.1 – 15.9 N-m). There was more tendency for a 90:10 or 95:5 (TF:KB w/w) sod mixtures to have higher sod strength than 100% TF sod. In Chapter 3, there were differences in sod strength among KB cultivars (~22 to 38 N-m, required work to tear; 389 to 568 N of maximum tensile load to tear sod), rhizome characteristics (rhizome number, length etc.) and germination and establishment vigor. Kentucky bluegrass classifications was not a good indicator for cultivar selection. In Chapter 4, RTF monostands did not produce similar high sod strength compared to 100% KB sod. Short rhizome lengths (<5 mm) were observed in RTF compared to >70 mm for KB. Differences were observed in germination (5 – 10 d) and establishment vigor (10 – 15 d) of RTF when compared to KB.
Keywords: Establishment vigor; Germination vigor; Harvest; Rhizome; Sod handling